Development of Rain Detector System using ESP32 With Alarm and Blynk Application - Bin Zulkiflee, Ahmad Luqman; Binti Sahadan, Puteri Aisyah Nur Dinie; Binti Rosmadi, Nur Fathiah; Bin Ismail, Muhammad Faizal (Multidisciplinary Applied Research and Innovation, 2022)
So, here is the innovation of Rain detector system and BLYNK application, which aims to help housewives overcome this problem by giving them a warning through the application BLYNK about the situation outside their home. If it is raining outside, the rain detector will send a notification "It’s raining!" to the user’s phone and a rain detector alarm will sound. With this, they can take further action immediately. So, this project describes the early design and development of an IoT (Internet of Things) project which is Rain Detector System for Smart Homeuser. This system uses a Rain Detector Sensor to detect the presence of the rain and send notification to the user. These project use ESP32 Module as themicrocontroller to store the data and send the notification from Blynk Application.